Kepemimpinan Manajerial dalam Meningkatkan Mutu Pendidikan Tinggi: Tela’ah Kritis Augustus E. Osseo Asare - Mujib Ustmani (Tarbiyah Departement collaboration with AMCA, 2013)
This critical study examines the relationship between efficiency and effectiveness of the quality management practices adopted by the UK, how quality management practices and the relationship between management efficiency